Efficiency of Semi-Automatic Banana Horn Cutting Machine - Mohamad, Mahmod Abd Hakim (Multidisciplinary Applied Research and Innovation, 2023)
A slicer is a device that can slice fruit, usually for the manufacturing of fried chips. The manual method of slicing a banana requires a lot of time and energy, and small and medium-sized businesses (SME's) in Malaysia no longer use it. Low operating costs are the primary goal of SME manufacturing processes, so this sector has a demand for low-cost, practical, and effective banana slicing equipment. However, starting a small firm cannot afford to purchase a fully automatic equipment because they are more expensive to maintain and require skilled operators. The aim of this project is to offer an alternate method for SME's to produce banana chips by developing and testing a semi-automatic slicer. The objectives are to create a semi-automatic slicer, test its functionality using a parametric approach, and assess how well it works. The machine can slice bananas and has a semi-automatic function. It is also user-friendly. To create a completely functional machine, the machine development process entails machine design using SolidWorks, material selection, metal works fabrication, which includes machining, cutting, and welding, assembly, testing, and remodification stages. The slicer was found to be capable of cutting the banana to the appropriate thickness during the machine test for slicing performance. When compared to the manual method, the time required to slice the fruits is 66 percent faster, which is a major improvement. Estimated at 55.71 N.m is the output torque determined from the design specification. The average slice thickness produces by the machine for bananas is 1.3 mm.